KEBEBASAN BERKONTRAK DALAM JUAL BELI MENURUT KITAB UNDANG-UNDANG HUKUM PERDATA DAN KOMPILASI HUKUM EKONOMI SHARIAH - Sukardi Sukardi (Al-Maslahah : Jurnal Ilmu Syariah, 2016)
This article discusses the right to draw up a sale contract according to Indonesian civil code and the law compilation of Islamic economy. This right includes a statement that everyone is free to draw up a contract as long as it is not against laws, norms, and social order. The right to draw up a contract is stated in Indonesian civil code, article 1493 in connection with article 1338 clause (1). However, the contract must be based on conditions mentioned in article 1320. Meanwhile, according to the law of Islamic economy, the right to draw up a contract (Huriyyatul Aqad) must be in accordance with social system, ethics, and sharia - in other words, a contract drawn up against sharia is unacceptable. Keywords: Freedom of contract, buy and sell, Kitab Undang-Undang Hukum Perdata, Hukum Ekonomi Shariah.